# SOLUTION: Which expression results from dividing 6x to the 8th power - 4x to the 6th power by 2x to the second power? f. -x to the sixth g. x to the fourth h.-3x to the fourth - 2x to

Algebra ->  Algebra  -> Equations -> SOLUTION: Which expression results from dividing 6x to the 8th power - 4x to the 6th power by 2x to the second power? f. -x to the sixth g. x to the fourth h.-3x to the fourth - 2x to       Log On

 Ad: Algebrator™ solves your algebra problems and provides step-by-step explanations! Ad: Algebra Solved!™: algebra software solves algebra homework problems with step-by-step help!

 Algebra: Equations Solvers Lessons Answers archive Quiz In Depth

 Question 484789: Which expression results from dividing 6x to the 8th power - 4x to the 6th power by 2x to the second power? f. -x to the sixth g. x to the fourth h.-3x to the fourth - 2x to the third i.3x to the sixth - 2x to the fourth. Answer by stanbon(57246)   (Show Source): You can put this solution on YOUR website!Which expression results from dividing 6x to the 8th power - 4x to the 6th power by 2x to the second power? --- [6x^8 - 4x^6)/2x^2 = 3x^6 -2x^4 ================================== Cheers, Stan H. ================================== f. -x to the sixth g. x to the fourth h.-3x to the fourth - 2x to the third i.3x to the sixth - 2x to the fourth.